IMPLEMENTATION OF ONLINE LEARNING IN LIGHT VEHICLE MACHINE MAINTENANCE SUBJECTS - Fadillah, Usman; Solehudin, Agus; Sukrawan, Yusep (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
This study aims to determine the implementation of e-learning-based learning on the light vehicle engine maintenance lesson, through the planning aspect which includes planning supervision, implementation, and learning evaluation. This study uses quantitative descriptive method. This study took a sample of 4 light vehicle engine maintenance teachers, 32 students, and the principal. The findings of this study showed that the lesson planning which carried out by the teachers was included as good category, the implementation of e-learning-based learning was included as quite good category, the learning evaluation was included as good category, and the planning supervision that is carried out by the principal was included as very good category.